The Impact of the COVID-19 Pandemic on Parkinson's Disease Patients in the Rural Midwest: A Mixed Methods Study - Maria Andrea Garcia Elizondo B.A.; Juliana de Almeida Cardoso Ph.D.; Lorraine Edwards M.D.; Jermaine Francis Jr., B.A. (Undergraduate Research Journal for the Human Sciences, 2025)
The COVID-19 pandemic brought challenges for individuals with Parkinson’s disease (PD). This concurrent mixed methods study explored the perceived pandemic’s impact on the quality of life and functional ability of individuals with PD in the rural Midwest. Thirty-one participants with Parkinson’s disease (Mage=73.48, SDage=7.18) completed the quantitative stage, which included measures of self-reported daily functioning. There was no statistically significant difference in self-reported daily functioning between participants who perceived they have had COVID and those who did not, t(29)=-.27, p=.46. Twenty-two participants completed semi-structured interviews that explored perceived quality of life. Thematic analysis identified five themes: symptom overlap, varied pandemic reactions, health literacy challenges, dimensions of isolation, and diverse perceptions of physical and emotional well-being. Findings highlight the multifaceted characteristic of quality of life, the need for comprehensive interdisciplinary approaches, peer support, and community-based programs to address the complex needs of PD patients.
Keywords: Parkinson’s disease; COVID-19; rural health; quality of life; mixed methods.